Mobility Patterns and Experiences of the Middle Classes in a Globalizing Age : the Case of Mexican Migrants in Australia - Vazquez Maggio, Monica Laura (Springer International Publishing, 2017)
The book presents insights from a mixed methodology study that examines recent mobility patterns exhibited by the middle classes. Its major contributions are two-fold: theoretically, it advances the conceptualisation of middle class migration; empirically, it analyses the migratory motivations of a relatively new Latin-American group in Australia. The accelerated insertion of the Mexican society into globalisation processes is strongly linked not only to the growing participation in migration phenomena but also to people's outflow to new destinations. Although studies of Mexican emigration are vast, research on Mexican skilled migration is scarce, and research that focuses on mobility to non-USA destinations is even scarcer. Mexicans are a relatively new addition to Australia's multicultural society, and little is known about this group's profile and why they choose to migrate to Australia. Employing a mixed methodology approach, the book provides a comprehensive portrait of migration in a new group.
Keywords: Mexicans -- Australia.; Mexicans -- Australia -- Social conditions.; Emigration and immigration.; Australia.; elektronické knihy; electronic books